Fundamentals of Thermodynamics [7th Ed.] - Borgnakke, Claus; Sonntag, Richard E. (New Delhi: Wiley, 2009)
Fundamentals of Thermodynamics is a comprehensive book for undergraduate students of Mechanical Engineering. The book comprises chapters on the first law of thermodynamics, first law analysis for a control volume, second law of thermodynamics, entropy, irreversibility and availability, phase change, gas mixtures, and chemical reactions. In addition, the book consists of several worked-out examples, problems, illustrations, and a rich selection of web-based learning resources for the students to understand the concepts better. This book is essential for engineering students preparing for the Graduate Aptitude Test in Engineering.
Keywords: Thermodynamics; Mechanical Engineering